Implementasi GMP, SSOP, HACCP Pada Pengolahan Ikan Tuna Sirip Kuning (Thunnus albacares) Beku di UD Damena - I Made Rya Prinata; Ni Made Darmadi; I Made Kawan (GEMA AGRO, 2025)
Fish contains essential amino acids, such as lysine, tryptophan and methionine. Therefore, to maintain the condition of the fish so that it remains fresh, it is necessary to carry out good post-harvest handling of the fish. This is done to avoid damage to the fish that can occur due to environmental conditions or microbial activity.The purpose of the research is to investigate and analyze the implementation of GMP, SSOP, and HACCP. The method used in this research is descriptive research method, to find out the description of the implementation of GMP, SSOP, HACCP in handling frozen yellowfin tuna (Thunnus albacares) at UD Damena. Data collection techniques used in research are observation, interviews, participation and documentation.Based on the research results, it is known that UD. Damena has fulfilled the basic requirements in the form of GMP and SSOP in accordance with KP Ministerial Regulation Number 17 of 2019. UD. Damena also implements the five steps and seven HACCP principles properly in accordance with SNI 01-4852-1998 as a form of consumer protection in the consumption of fishery products so that export activities run effectively and efficiently without any cases of product rejection in the destination country. Implementation of GMP and SSOP systems at UD. Damena has been implemented well and optimally. Implementation of HACCP at UD companies. Damena has been implemented properly, by coordinating with the HACCP team. .